Development of online scheduled waste collection system from households / Azree Azhar Awi - Azree Azhar, Awi (2022)
In 2020, more than 70,000 tonnes of scheduled waste were generated from Malaysian households. From this, used cooking oil make up almost 85%, while more than 10% are electronic wastes and the rest are used paint, pesticides, solvents, used lubricants and others. Nowadays, most household cooking oil are stored in plastic bottles or containers, although it was found that used cooking oil was also disposed into kitchen sinks as traces of the oil have been found in municipal drainage systems. Used cooking oil that flow into the kitchen sink and enter plumbing systems would eventually clog the wastewater outflow due to prolonged sedimentation. After which, plumbing systems become dirty and smelly inside. As for other scheduled household waste, it is common that they are stored in garbage bags mixed with other solid waste such as food waste and plastic film, before being disposed. The mixed solid waste is then collected by municipal dump-trucks to be transported to municipal landfills. Later, it becomes a problem for landfill operators to segregate the scheduled waste from the solid wastes. Currently, only industrial and companies’ scheduled waste are compulsory to be reported and collected through a web system called the ESWIS while no systems are available for households to report and collect their scheduled waste. To meet the paper objectives, a series of hypothesis validation method has been done with selected households within the target area. Issues and major problems have been identified while conducting the validation study. Based on the analysis, 93% of households validate the use of the online scheduled waste collection system because it is more user-friendly and easier to use than existing methods. At least 80% of homes have sent their scheduled waste to recycling centres, indicating that the majority of families are aware of the importance of waste recycling. However, the majority of households were unaware of the scheduled waste collection service, and at least 73% of them believe that engaging the current booking service is difficult owing to unclear procedures and insufficient communication. The implementation of the online system will save 3500 tonnes of scheduled waste from households every year from being dump to the environment. .